2022
DOI: 10.1111/hepr.13859
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of switching to pemafibrate from bezafibrate in patients with chronic liver disease

Abstract: Aim Although fibrates were developed as lipid‐lowering drugs, their efficacy against liver dysfunction in patients with cholestatic liver diseases, such as primary biliary cholangitis, primary sclerosing cholangitis, and fatty liver disease, has also been reported. Although fibrates act on some peroxisome proliferator‐activated receptors (PPARs), pemafibrate is a novel selective PPAR‐α modulator. The present study aimed to evaluate the safety and efficacy of switching from bezafibrate to pemafibrate in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Pemafibrate, a new selective PPARα modulator, was recommended for treating PBC with dyslipidemia, or for patients with poor response to UDCA monotherapy or bezafibrate plus UDCA combination treatment ( 141 ). It is also noted that switching from Fenofibrate or bezafibrate to Pemafibrate reduced adverse effects for patients with incomplete response or some renal disorder ( 142 , 143 ).…”
Section: Targeting Bile Acid Metabolismmentioning
confidence: 99%
“…Pemafibrate, a new selective PPARα modulator, was recommended for treating PBC with dyslipidemia, or for patients with poor response to UDCA monotherapy or bezafibrate plus UDCA combination treatment ( 141 ). It is also noted that switching from Fenofibrate or bezafibrate to Pemafibrate reduced adverse effects for patients with incomplete response or some renal disorder ( 142 , 143 ).…”
Section: Targeting Bile Acid Metabolismmentioning
confidence: 99%
“…Pemafibrate is a selective peroxisome proliferator-activated receptor (PPAR) α modulator that was designed to have greater PPARα agonistic activity and selectivity than existing PPARα agonists [7,8]. Recent animal studies suggest that PPARα has anti-inflammatory properties through transrepression of pro-inflammatory target genes, such as activator protein (AP)-1 and nuclear factor (NF)-κB [9].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic evaluation of pemafibrate in nonalcoholic fatty liver disease-related cardiovascular diseases Tamai and Okamura indicated that the novel selective peroxisome proliferator-activated receptor (PPAR)α modulator, pemafibrate improved adverse effects and incomplete response, and had more beneficial safety and efficacy in patients with chronic liver diseases compared with bezafibrate, including creatinine, hemoglobin, and estimated glomerular filtration rate. 1 Moreover, the therapeutic response of pemafibrate was superior to bezafibrate in the improvement of metabolism dysfunction-related cardiovascular events due to enhanced PPARα activity and specificity, 2 but the effects of pemafibrate on the metabolic association between chronic liver diseases and cardiovascular diseases (CVD) were not investigated and should be emphasized. Thus, I have some opinions on the metabolic modulation of pemafibrate against nonalcoholic fatty liver disease (NAFLD)-related CVD.…”
mentioning
confidence: 99%